Investigation of grain growth and magnetic properties of low-sintered LiZnTi ferrite-ceramic. Issue 10 (July 2020) - Xu, Fang; Shi, Xiaolei; Liao, Yulong; Li, Jie; Hu, Jianbo
Abstract: LiZnTi ferrite-ceramics with good magnetic properties and high Curie temperature have been widely studied and utilized in microwave devices. However, it is necessary to further lower sintering temperature and enhance magnetic properties of the ferrites to meet the requirements of practical application. Here, fully dense LiZnTi ferrite-ceramic with high saturation magnetization (4π M s ) and high saturation flux density ( B s ) is synthesized through solid phase reaction, using low-melting V2 O5 additive. Results indicate that the LiZnTi ferrite-ceramic sintered at 925 °C has dense microstructure. Also, average grain size, B s and 4π M s of the sample increase to 6.38 μm, 324.4 mT and 4277 Gs when the amount of V2 O5 increases from 0.00 wt % to 0.40 wt %, respectively. Interestingly, second grain growth occurs when the amount of V2 O5 additive increases to 0.60 wt %. Although the competitive second grain growth results in many small grains, the LiZnTi ferrite still has acceptable magnetic properties ( B s =316.3 mT; 4π M s =4072 Gs). The characteristic of second grain growth can allow the development of V2 O5 -based composite additive for fabricating uniform and dense ceramic materials with enhanced properties, especially for ferrite materials.